"Risky interactions" relationships between contemporary art and education (DAPesquisa, 2020)
With the intention of contributing to the discussions that happen in academic fields about how to insert contemporary art in education, and to defend the notion that the art of today is closer to the day-to-day, in this text are commented the artistic processes of four contemporary artists that use in their poetics the most indispensable element for life: the water. Contemporary art is contextualized, initially highlighting the changes that have occurred in recent times, including those resulting from new technologies. It is concluded that the current public politics for education are in the opposite direction of what art offers, as well as that teachers must understand the new logic in force to take advantage of the potential of current art.